Genotoxic potential of leaf extracts of Jatropha gossypiifolia L. - Almeida, P. M.; Araujo, S. S.; Santos, I. R. M. R.; Marin-Morales, M. A. [UNESP]; Benko-Iseppon, A. M.; Santos, A. V.; Randau, K. P.; Brasileiro-Vidal, A. C. (Funpec-editora, 2016)
Jatropha gossypiifolia L. (Euphorbiaceae) is widely used in popular medicine. However, further toxicological studies are necessary for its reliable use. The present study aimed to evaluate the cytotoxic, genotoxic, and mutagenic effects of ethanolic and aqueous leaf extracts of J. gossypiifolia, using the test system Allium cepa. In addition, the phytochemical profile of the extracts was also obtained. Seeds of A. cepa were subjected to different concentrations of the two extracts (0.001, 0.01, 0.1, 1, and 10 mg/mL). Distilled water was used for the negative control and methyl methanesulfonate (4 x 10(-4) M) and trifluralin (0.84 ppm) for the positive controls. The values of mitotic index at all concentrations of ethanolic extract and at 0.1, 1, and 10 mg/mL aqueous extract showed a significant decrease. Alterations, such as chromosome adherence, C-metaphases, chromosome bridges, nuclear buds, and micronuclei were verified in both extracts but chromosome loss indicating genotoxic activity was observed only in the ethanolic extract. Presence of micronuclei on administration of the extracts, also indicated mutagenic action at the chromosome level. In the ethanolic extract, aneugenicity seemed to be the main activity, probably as a result of the action of terpenes and/or flavonoids, whereas in the aqueous extract, clastogenic action appeared to be the principal activity, presumably as a consequence of the effect of flavonoids and/or saponins. Thus, we suggest that the extracts of this species should be used with great caution for medicinal purpose.
Keywords: Chromosome alterations; Aqueous extract; Ethanolic extract; Phytochemical profile; Allium cepa test